Quark-hadron duality at work: lifetimes of bottom baryons - James Gratrex; Alexander Lenz; Blaženka Melić; Ivan Nišandžić; Maria Laura Piscopo; Aleksey V. Rusov (Journal of High Energy Physics, 2023)
Abstract In the 1990s, very low experimental values for the lifetime ratio τ(Λ b )/τ(B d ) triggered a considerable amount of doubt in the applicability of the heavy quark expansion (HQE), which is based on the assumption of quark-hadron duality (QHD) for inclusive total decay rates. However, these low values turned out to be the result of purely experimental problems, and the current HFLAV average reads τ(Λ b )/τ(B d ) = 0.969(6). In this work, we present the Standard Model predictions for the b-baryon lifetimes within the framework of the HQE. In particular, we include for the first time the contribution of the Darwin term and we update the estimates for the matrix elements of the dimension-six four-quark operators. Within experimental and theoretical uncertainties, we find excellent agreement between the data and the HQE predictions, and thus no indication for any visible violation of QHD. Our numerical results can be summarised by the ratios τ(Λ b )/τ(B d ) = 0.955(14), τ Ω b − $$ \tau \left({\varOmega}_b^{-}\right) $$ /τ(B d ) = 1.081(42), and τ Ξ b 0 / τ Ξ b − $$ \tau \left({\Xi}_b^0\right)/\tau \left({\Xi}_b^{-}\right) $$ = 0.929(28).